A Systematic Review of Leadership and Safety Management System in Air Transportation - Krishananta Wijaya; Dwi Utami Puterisari (PT Publikasiku Academic Solution, 2025)
This study aims to perform a thorough analysis of the connection between leadership and the effectiveness of safety management systems (SMS) in aviation. The analysis examines how different leadership philosophies, such as paternalistic and transformational approaches, affect SMS deployment and safety culture in airport, airline, and air traffic control settings. Twenty-one pertinent papers from national and international sources, published between 2019 and 2025, were selected using a systematic literature review (SLR) procedure based on the PRISMA methodology. The results show that implementing SMS principles requires strong leadership behavior. Although contextual leadership approaches, such as paternalistic leadership in air traffic control, also have a positive influence, transformational leadership is the most effective at enhancing safety outcomes. The evaluation highlights the significance of human-centered leadership for successful implementation and identifies a significant gap in the combination of technology-based safety enhancements and leadership. This study offers a conceptual framework that views leadership as a vital facilitator of aviation safety, providing guidance to academics and industry professionals looking to enhance safety performance through leadership practices.